Strategi Pengelolaan Badan Usaha Milik Desa (BUMDES) untuk Kesejahteraan Masyarakat dalam Perspektif Ekonomi Islam di Desa Mpili Kec. Donggo - Iransayah; Muhammad Rasyad Al, Fajar; Muhammad Zia Ulhaq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
Mpili village is a population and group that can really overcome prosperity and achieve national development targets The village government provides funds to manage the government to develop several economic activities in the community and maximize community opinion titles to be able to meet the needs and potential of the village. So this research aims to the Management Strategy of Village-Owned Enterprises (Bumdes) for Community Welfare in the Perspective of Islamic Economics in Mpili Village, Donggo Kec. This research will be conducted in Mpili Village, Donggo Subdistrict, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Descriptive Approach. Data Collection Techniques are Observation and Interview. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the study, it can be concluded that the BUMDes management strategy in Mpili Village has shown a fairly positive development direction, although it is still in the growth stage. The village government together with the community has succeeded in building a business management system that optimally utilizes local potential, especially in the agriculture and trade sectors.